Whole Exome Sequencing Identifies TTC7A Mutations for Combined Immunodeficiency with Intestinal Atresias - Chen, Rui (2013)
BACKGROUND: Combined Immunodeficiency with Multiple Intestinal Atresias (CID-MIA) is a rare hereditary disease characterized by intestinal obstructions and profound immune defects. OBJECTIVE: We sought to determine the underlying genetic causes of CID-MIA by analyzing the exomic sequence of 5 patients and their healthy direct relatives from 5 unrelated families. METHODS: We performed whole exome sequencing on 5 CID-MIA patients and 10 healthy direct family members belonging to 5 unrelated families with CID-MIA. We also performed targeted Sanger sequencing for the candidate gene TTC7A on 3 additional CID-MIA patients. RESULTS: Through analysis and comparison of the exomic sequence of the individuals from these 5 families, we identified biallelic damaging mutations in the TTC7A gene, for a total of 7 distinct mutations. Targeted TTC7A gene sequencing in 3 additional unrelated patients with CID-MIA revealed biallelic deleterious mutations in two of them, as well as an aberrant splice product in the third patient. Staining of normal thymus showed that the TTC7A protein is expressed in thymic epithelial cells as well as in thymocytes. Moreover, severe lymphoid depletion was observed in the thymus and peripheral lymphoid tissues from two patients with CID-MIA. CONCLUSIONS: We identified deleterious mutations of the TTC7A gene in 8 unrelated patients with CID-MIA and demonstrated that the TTC7A protein is expressed in the thymus. Our results strongly suggest that TTC7A gene defects cause CID-MIA. CLINICAL IMPLICATIONS: Damaging mutations in the gene TTC7A should be scrutinized in patients with CID-MIA. Characterization of the role of this protein in the immune system and intestinal development, as well as in thymic epithelial cells may have important therapeutic implications.